Response to apatinib and camrelizumab combined treatment in a radioiodine refractory differentiated thyroid cancer patient resistant to prior anti-angiogenic therapy: A case report and literature review - Li, Jiayi; Zhang, Xin; Mu, Zhuanzhuan; Sun, Di; Sun, Yuqing; Lin, Yansong (Frontiers in Immunology, 2022)
Background Patients with radioactive iodine refractory progressive (RAIR) differentiated thyroid cancer (DTC) often developed resistance after first-line therapy. Apatinib plus camrelizumab is a therapy with promising efficacy in patients with other malignant cancers. Herein, we presented a case of progressive RAIR DTC treated with apatinib plus camrelizumab. Case presentation We reported a 43-year-old man diagnosed as DTC with metastases in the lungs, the 7th cervical vertebra, and malignant lymph nodes mainly in the mediastinum. While initially showing disease stabilization after giving the first-line multitargeted kinase inhibitor (MKI) therapy, the patient developed progressive disease and was enrolled into a combined therapy with both apatinib and camrelizumab on November 10, 2020. Upon the first 6 months, the combination therapy showed disease control in terms of both stable structural lesions and biochemical thyroglobulin (Tg) level. Six months later, a decrease over the targeted lesions was observed and a partial response (PR) according to RECIST 1.1 criteria was finally achieved upon 12 months’ assessment, followed by the decline in serum Tg level. The main adverse event was occasional diarrhea without treatment interruption. Conclusion We reported a case with RAIR DTC that benefited from combination immunotherapy, apatinib plus camrelizumab, after resistance from donafenib. We observed a gradually getting better efficacy and a mild and long duration of this combination therapy and hoped to provide a therapeutic choice for these patients.